2009
DOI: 10.1007/s00125-009-1617-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose level on early and long-term mortality after intracerebral haemorrhage: the Acute Brain Bleeding Analysis Study

Abstract: Aims/hypothesis Admission hyperglycaemia is associated with a poor outcome in patients with ischaemic stroke. However, its prognostic effects after intracerebral haemorrhage (ICH) are still unclear. Methods We prospectively enrolled patients with ICH at 33 centres in Korea between October 2002 and March 2004. A total of 1,387 patients who had ICH and underwent brain computed tomography within 48 h of symptom onset were included in the study (n=1,387). Clinical information and radiological findings were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 25 publications
3
46
0
Order By: Relevance
“…Our findings extend previous reports of elevated blood glucose being a predictor of adverse outcomes in ICH 8,9,13,14 ; in particular, the finding of a trend toward greater mortality from hyperglycemia that was observed in Korean multicenter study 9 of 1387 ICH patients, but not with that seen in a smaller Finnish study. 13 Sensitivity analysis of outcomes based on diagnostic thresholds (reference group <6.1 mmol/L) of blood glucose rather than fourths (reference group of 2.6-5.6 mmol/L) potentially allowed more clinically relevant glucose levels to be assessed.…”
Section: Downloaded Fromsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings extend previous reports of elevated blood glucose being a predictor of adverse outcomes in ICH 8,9,13,14 ; in particular, the finding of a trend toward greater mortality from hyperglycemia that was observed in Korean multicenter study 9 of 1387 ICH patients, but not with that seen in a smaller Finnish study. 13 Sensitivity analysis of outcomes based on diagnostic thresholds (reference group <6.1 mmol/L) of blood glucose rather than fourths (reference group of 2.6-5.6 mmol/L) potentially allowed more clinically relevant glucose levels to be assessed.…”
Section: Downloaded Fromsupporting
confidence: 89%
“…9 Animal models have shown that elevated blood pressure (BP) exacerbates cerebral injury after ICH 10 and of an association between hyperglycemia and cerebral edema. There may be a supra-additive effect of hyperglycemia and Background and Purpose-We aimed to determine associations of baseline blood glucose and diabetes mellitus with clinical outcomes in participants of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT2).…”
mentioning
confidence: 99%
“…A large number of observational studies (21 studies, total number of patients=12 145, Table S6)2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32 have examined the association between glucose with ICH outcome with the majority (15 studies, total n=11 161) defining hyperglycemia on the basis of single glucose measurement. One notable study was the post hoc analysis of the Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT) II study (n=2653) 30.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus and hyperglycemia are associated with a worse prognosis of ICH 27,28 and an increased rate of hemorrhagic transformation after systemic thrombolysis in patients with ischemic stroke. 29,30 Although direct influences on the coagulation system may at least partially explain the increased bleeding risk, 31 several studies showed that macrophage responses critical for wound healing are also impaired in diabetes mellitus.…”
Section: Strokementioning
confidence: 99%